ChemInform Abstract: A Novel and Efficient Synthesis of 2‐Substituted Quinazolin‐4(3H)‐ones by the Reaction of (Het)arylmethanamines with Isatoic Anhydride. Issue 49 (17th November 2016) - Mahdavi, Mohammad; Hassanzadeh, Rasool; Soheilizad, Mehdi; Golshani, Shiva; Moghimi, Setareh; Firoozpour, Loghman; Shafiee, Abbas; Foroumadi, Alireza
Abstract: The one‐pot reaction between isatoic anhydride (I) and benzylamines (II) leads to the formation of N‐substituted anthranilamides, which under aerobic conditions in the presence of CuBr undergo an in situ oxidation ‐ cyclization sequence to afford title compounds (III) in good yields.